Filter bank design for receiver back ends of satellite constellations - Jakobsson, Måns; Rajan, Amritha (My University, 2022)
Weather forecasting using satellites has been of great interest, since climate change is a global threat. There is also a need to make sustainable designs and reduce power consumption, size etc. This thesis presents the receiver back-end design (IF Block) for faster weather forecasting in satellite constellations. The suggested prototype called Weather Cube, has been able to meet most of the design goals. The first step of this thesis, was reviewing the existing design of the Arctic Weather Satellite and identifying what could be changed. Certain methods to reduce the power consumption for the back-end of the Arctic Weather Satellite, while maintaining the system performance are presented. Amplifiers present in the RF Section were the main reason of power consumption. There are amplifiers present in each channel for both gain levelling and isolation. Initially, the number of amplifiers were reduced and attenuators were added for gain levelling, but that didn’t satisfy the isolation requirements. Different components were explored to test ideas. The final decisionn was to replace multiple amplifiers used for isolation in the system, with passive isolators. This reduces the power consumption significantly, while fulfilling the requirements for isolation. Bulky, coaxial components like diplexers are also replaced with a simpler system of a resistive divider and filters. The performance of a diplexer is better than this system, in terms of insertion loss and isolation but the resistive divider and high pass/low pass filters can be surface mounted. The insertion loss due to the resistive divider can be compensated for with more amplification in the system and isolation can be achieved with divider and filters combination. Transmission lines are also tuned to minimize reflections. There are certain trade-offs when design choices were considered, which are also a part of this report. All components were tested by designing individual PCBs, and the measurements were then simulated in Microwave Office. The transmission lines for channel performance, were optimized in Microwave Office to attain better results. The measurements can be improved further by designing the whole PCB. Another future improvement is linked to one of amplifiers used in the system, ADL9005, this amplifier is now operated at 3 V and 20 mA and has a certain amount of ripple, but it’s possible to test it further by changing the bias resistor to vary the current and in turn gain. The isolators are a relatively new component and is not frequently used in space-systems, different mounting strategies could be tested later to see if the performance can be improved.
Keywords: weather forecasting, isolator, diplexer, IF block, amplifiers, power consumption, size, Microwave Office, Weather Cube, Arctic Weather Satellite, resistive dividers